Case Report: Afatinib-Induced Interstitial Pneumonia: Experiences and Lessons From Two Patients - Liu, Xiao; Ma, Baozhen; Li, Tiepeng; Zhao, Lingdi (Frontiers in Pharmacology, 2021)
Background: Afatinib has shown good efficacy in patients harboring uncommon EGFR mutations, but the incidence of afatinib-induced interstitial pneumonia should be alert as its rapid progression. Here, we report two cases of interstitial pneumonia during afatinib treatment. Case presentation: The first case was of a 58-year-old male with advanced lung adenocarcinoma (cT4bN3M1b) with exon 18 G719X and exon 20 S781I EGFR mutations and received afatinib therapy. After 68 days of therapy, he developed shortness of breath and fever. Drug-induced pneumonia was not diagnosed timely, the patient received empirical antibiotics and low-dose glucocorticoids. The pulmonary inflammation rapidly progressed and the patient died 15 days after symptom onset. The second case was of a 57-year-old man with stage IV (cT3N3M1b) lung adenocarcinoma with exon 21 L861Q EGFR mutation. He received afatinib as second-line therapy. Fever and shortness of breath occurred 22 days after afatinib therapy, he received empirical antibiotic therapy. Five days later, CT showed aggravated pulmonary inflammation, and afatinib-induced interstitial pneumonia was diagnosed. He received glucocorticoid therapy, and the pneumonia quickly improved. Conclusion: Although the incidence of EGFR-TKI-associated pneumonia is uncommon, high vigilance for drug-induced interstitial pneumonia is necessary during treatment. Early diagnosis and early glucocorticoid therapy could reverse lung injury.